2013
DOI: 10.1371/journal.pone.0074162
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Defect Is Associated with Low Glucose-Induced Apoptosis in 661W Photoreceptor Cells

Abstract: Glucose is an important metabolic substrate of the retina and diabetic patients have to maintain a strict normoglycemia to avoid diabetes secondary effects, including cardiovascular disease, nephropathy, neuropathy and retinopathy. Others and we recently demonstrated the potential role of hypoglycemia in diabetic retinopathy. We showed acute hypoglycemia to induce retinal cell death both in vivo during an hyperinsulinemic/hypoglycemic clamp and in vitro in 661W photoreceptor cells cultured at low glucose conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 50 publications
(66 reference statements)
3
33
0
Order By: Relevance
“…Thus, we demonstrated that impaired autophagic flux by BPA enhances apoptosis by elevating the levels of cleaved caspase-3. Several studies report that autophagy impairment increases caspase-3 activity and cell death (72,92). Interestingly, long term exposure of BPA caused hippocampal neurodegeneration and reduced learning and memory ability in the rats.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we demonstrated that impaired autophagic flux by BPA enhances apoptosis by elevating the levels of cleaved caspase-3. Several studies report that autophagy impairment increases caspase-3 activity and cell death (72,92). Interestingly, long term exposure of BPA caused hippocampal neurodegeneration and reduced learning and memory ability in the rats.…”
Section: Discussionmentioning
confidence: 99%
“…This implies the effect of Atg7 deficiency on the cell cycle may associate with glucose starvation. The data supports a study by Balmer et al (19) which indicated that low glucose-induced apoptosis with inhibition of autophagy may lead to cell death in 661W photoreceptor cells. Ramírez-Peinado et al (20) hypothesized that autophagic flux induced by other stimuli is inhibited in the absence of glucose.…”
supporting
confidence: 91%
“…In retinal cells, low glucose-induced apoptosis is involved in autophagosome formation through the AMPK/ RAPTOR/mTOR pathway [88]. The specific inhibition of autophagy, either by 3-MA or the downregulation of ATG5 or ATG7 protein expression, increased caspase 3 activation and induced 661W cell death.…”
Section: Cross-talk Between Autophagy and Apoptosismentioning
confidence: 99%
“…The specific inhibition of autophagy, either by 3-MA or the downregulation of ATG5 or ATG7 protein expression, increased caspase 3 activation and induced 661W cell death. These results suggest that cells struggle against low nutrient-induced apoptosis by initiating an autophagic process but failed to survive when autophagy is inhibited [88]. In murine cytomegalovirus-induced retinal apoptosis, autophagy induced by rapamycin inhibited apoptosis [89].…”
Section: Cross-talk Between Autophagy and Apoptosismentioning
confidence: 99%